2020
DOI: 10.3390/su12114340
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Perspective in Public Educational Institutions Restaurants: From Foodstuffs Purchase to Meal Offer

Abstract: This study aimed to evaluate aspects of sustainable nutrition in Public Educational Institutions Restaurants (PEIR) in a Brazilian state. Cross-sectional descriptive research was conducted in six PEIR. Purchased foodstuffs for a one-month period were investigated from the perspective of their origin (place of production), processing degree and nutritional profile. The presence of Genetically Modified Organisms (GMO) in packaged foodstuffs was also evaluated. Regarding served meals, a four-week period was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Studies have shown that meats and processed meat products purchased by public education institutions are rarely local in origin [61,62]. However, this group of foods still features within the scope of supply of family farming in the public calls, also with special attention to processed foods [49], signaling that there is potential for the distribution and production of different food groups by family farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that meats and processed meat products purchased by public education institutions are rarely local in origin [61,62]. However, this group of foods still features within the scope of supply of family farming in the public calls, also with special attention to processed foods [49], signaling that there is potential for the distribution and production of different food groups by family farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Many products used in enteral nutrition or infant formulas have water as their main component. In a study that evaluated 74 products available in Brazil, it was identified that 87.8% were marketed in liquid form 41 . Thus, a large part of the emissions is due to the transport of the main constituent: water.…”
Section: Supplementary Foodmentioning
confidence: 99%
“…Some of the most promising means to improve water use efficiency involve a combination of plant-based dietary choices and reducing food loss and waste. [184,[208][209][210][211][212][213][214] Water use efficiency: micronutrient output per liter consumptive water use.…”
Section: Environmental Concern Indicators and Definition Relevance And Comments Referencesmentioning
confidence: 99%